SOCIALIZATION AND EXAMINATION OF TREASURE MANAGEMENT AT GMIM MUSAFIR KLEAK MANADO - Lonto, Miryam Pingkan; O. Rengku, Jeffry (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Management treasury church is something important in a church service, because urgent for accountability to congregation or people. The newly elected treasurers or deacons come from diverse educational backgrounds. Only few treasurers or deacons have knowledge related with management finance specifically treasury church. Based on this background, this activity was carried out to provide an understanding of treasury managers at GMIM Musafir Kleak in accordance with the GMIM church order and improve the ability of treasury managers at GMIM Musafir Kleak in the aspects of recording, depositing, and reporting in accordance with GMIM church order. The activity was carried out in two stages, the first stage was socialization regarding treasury management in accordance with church regulations. The second stage is an examination of the treasury manager at GMIM Musafir Kleak. The results of this activity greatly impacted the treasurers and deacons, because they gained an understanding of how to properly record and manage the congregation's finances in accordance with church regulations. Recommendations have also been given for improving treasury management regarding financial management which is expected to have an impact on improving services at GMIM Musafir Kleak.